Detection on OAR7 of QTL affecting fat and protein yields in dairy sheep - Antonello Carta; Françis Barillet; Stefania Sechi; Giuliana Mulas; Maria Colombino; Sara Casu (Italian Journal of Animal Science, 2010)
The objective of this paper was identifying QTL that affect fat and protein yields in dairy sheep independently of milk yield. Data were collected in an experimental flock of 887 ewes organized in a daughter design. QTL detection focused on OAR7 where 13 microsatellites were available. The genetic abilities to produce fat and protein independently from the ability to produce milk were estimated as the residuals of the regression of EBV for fat and protein yields on EBV for milk yield. One QTL affecting fat yield (CWP=0.00009) and one QTL affecting protein yield (CWP=0.006) were detected. The most probable QTL location was 115.3 cM in the Sheep Best Position Linkage Map Version 4.7 for both traits. No QTL affecting milk yield was detected. The analysis of fat and protein yields independently of milk yield is an effective strategy to identify chromosomal regions affecting milk composition with no detrimental effect on milk yield.